Properties of sand cement brick containing ground palm oil fuel ash as fine aggregate replacement - Khairunisa, Muthusamy; Muhammad Azreen, Ibrahim; Nor Hazurina, Othman; Budiea, Ahmed Mokhtar Albshir; Saffuan, Wan Ahmad (TULPAR Academic Publishing, 2018)
The prosperous palm oil industry continues to generate increasing amount of palm oil fuel ash which disposed as environmental polluting waste. Thus, research was conducted to investigate the effect of ground palm oil fuel ash as partial fine aggregate replacement towards properties of sand cement brick. Series of mixes were prepared with 0%, 5%, 10%, 15%, 20% and 25% ground palm oil fuel ash partially substituting the river sand. Two types of curing methods were applied namely water and air curing. The bricks were subjected to compressive strength, flexural strength and water absorption test at 28 days. The results show that utilization of 15% ground palm oil fuel ash as fine aggregate replacement increases the brick strength. The pozzolanic reaction and filler effect of the finely ground ash makes the concrete internal structure denser resulting in strength enhancement. The use of ground palm oil fuel ash in brick production would reduce amount of palm oil waste disposed, save the use of land for dumping purpose and decrease quantity of river sand mined.